Nurse’s Competency Toward Covid-19: A Systematic Review - Hikmat Pramajati; Nunung Siti Sukaesih; Reni Nuryani; Emi Lindayani; Ahmad Purnama; Heri Ridwan; Thaofik Fauzi Nugraha; Irawan Danismaya; Halimatusyadiah Halimatusyadiah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Since the spread of the Covid-19 outbreak, nurses have been actively involved for 24 hours in providing nursing care to Covid-19 patients both in hospital and public health centers. As part of the front liner, the role of nurses during fighting against Covid-19 requires good knowledge and competence. This review describes the articles regarding nurses’ knowledge and competency toward Covid-19 that have been published. Methods: The research articles were retrieved from the Scopus database and Science direct database. Results: The major findings of the review showed that nurses almost have a good knowledge regarding the Covid-19 outbreak. However, it is widely reported that nurses are insufﬁciently trained. Most of them only read guidelines that have been established by the government. Furthermore, the nurses do not feel conﬁdent responding effectively to the Covid-19 pandemic. The other issues according to the articles were the need for support, motivation, material especially personal protective equipment so that the nurses would perform their role better. The result of the study contributes to the competency of Covid-19 pandemic preparedness among nurse professions. Conclusions : The findings of the study also would be evidence-based for the government, nurse managers to prepare nurses for fighting against outbreak response. According to the review, it is recommended that all nurses must be facilitated to get training or education periodically regarding Covid-19.